Elevated alanine aminotransferase independently predicts new onset of depression in employees undergoing health screening examinations. Issue 12 (December 2013) - Zelber-Sagi, S.; Toker, S.; Armon, G.; Melamed, S.; Berliner, S.; Shapira, I.; Halpern, Z.; Santo, E.; Shibolet, O.
<x content-type="archive" xml:space="preserve">Abstract</x> Background Non-alcoholic fatty liver disease (NAFLD) is the most common cause of elevated alanine aminotransferase (ALT). NAFLD is associated with insulin resistance and hepatic inflammation. Similarly, patients with depression exhibit insulin resistance and increased inflammatory markers. However, no study has shown a clear association between elevated ALT and the development of depression. The aim of the study was to test whether elevated ALT, a surrogate marker for NAFLD, predicts the development of depression. Method The present prospective cohort study investigated 12 180 employed adults referred for health examinations that included fasting blood tests and anthropometric measurements between 2003 and 2010. Exclusion criteria were: baseline minor/major depression, excessive alcohol consumption and other causes for ALT elevation. Depression was evaluated by the eight-item Patient Health Questionnaire (PHQ-8) score. Results The final cohort included 5984 subjects [69.4% men, aged 45.0 (s.d. = 10.24) years]. The incidence rate of minor and major depression was 3.8% and 1.4%, respectively. Elevated ALT was a significant independent predictor for the occurrence of minor [odds ratio (OR) 2.02, 95% confidence interval (CI) 1.40–2.92] and major (OR 3.132, 95% CI 1.81–5.40) depression after adjusting for age, gender, body mass index, education level, serum levels of lipids, glucose, smoking and physical activity. Adding subjective health and affective state parameters (sleep disturbances, self-rated health, anxiety and burnout) as potential mediators only slightly ameliorated the association. Persistently elevated ALT was associated with the greatest risk for minor or major depression as compared with elevation only at baseline or follow-up (p for trend < 0.001). Conclusions Elevated ALT was associated with developing depressive symptoms, thus suggesting that NAFLD may represent an independent modifiable risk factor for depression.